Pemanfaatan Jamur Tiram ( pleurotus ostreatus ) dan Ekstrak Daun Kelor sebagai Inovasi Bahan Tambahan Pembuatan Permen Jelly dengan Pewarna Alami Kulit Buah Naga - Istianah, Anisa Farkhatul, Dra. Aminah Asngad, M.Si (2016)
Jelly is a food product like everyone from the children to adults, are generally made from gelatin base material with the addition of gelatin as elastic. Making candy jelly in this study using a new innovation with the addition of oyster mushrooms to improve the nutritional value. In general, jelly using synthetic dyes that can endanger the health of consumers. Jelly fungi in this study using natural dyes from the skin of the dragon fruit. In addition to using oyster mushrooms and dragon fruit peel extract jelly also added Moringa leaf extract. Moringa leaf is a plant that many health benefits. The purpose of this study to determine the protein content, color, flavor, aroma, texture and elasticity of jelly. The method used was completely randomized design (CRD) with a pattern of two factors: factor 1, the addition of oyster mushrooms (A): 100 ml, 90 ml, 80 ml and a factor of 2, the addition of extracts of Moringa leaves and bark extracts dragon fruit (P): 50 ml and 15 ml, 60 ml and 25 ml, 70 ml and 30 ml. The results showed that the addition of oyster mushroom, extract of Moringa leaves and dragon fruit skin extracts significantly affect the color, flavor, aroma, texture and suppleness. A3P1 highest protein content is 10.95% and the lowest is 8.55% A3P2.